Create, Connect, Convince: Jörg Dietzel on Advertising, Branding and Communications - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2008)
Advertising veteran, Jörg Dietzel, runs his own company, Jörg Dietzel Brand Consultants, in Singapore and Jakarta. He also teaches classes in branding, advertising and communications at the Singapore Management University, and is currently hosting a four-part TV series, “The Consultant”, produced by Channel News Asia. Knowledge@SMU spoke to Dietzel about his new book, Create l Connect l Convince.